Shrek: do conto aos filmes, em uma sucessão de paródias - Souza, Denise Loreto de [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
We have seen from the last two decades of the 20th century, the rereading of the fairy tale genre both in literature aimed at children in cinema in general, and in the animated film in particular. I realize that the parodic procedure is present in the rereading process, being contemplated, in that gesture, some aspects of traditional fairy tales and lefting intacts other elements. It is from the question of how these narratives work to rereading of fairy tales that I begin the investigation that motivates this research project: how the narrative Shrek!, by William Steig, and its film adaptations, by Dreamworks Animation studios, proceed the genre rereading. The research will include, first, the study of the fairy tale genre, its structure and semantic aspects, from reading the narrative of Steig, to, then, investigate the textual dialogue between the work and the genre it belongs. Later, the story made into a film will be the subject of research to investigate how the fairy tale genre is rereaded by the cinema support from the ingredients provided by the narrative of Steig. I will take into account the stylistic aspects of speech, both the original English. With reference to the film adaptation, we will proceed the same way, but limited in scenes that will focus on as most important for analysis. I assume that the film version of the tale expands the rereading procedure, establishing a broader dialogue with the genre itself. I will concentrate on the nature of the Shrek character, built like an ogre, to check, among other things, the process of grotescalização by wich Steig conducts his text. I will investigate how the grotesque contributes to the rereading of the genre both in written narrative and in its film adaptation. I am, thereby, to contribute to studies of fairy tale genre and for literature studies aimed at children and young people

Temos assistido, desde as duas últimas décadas do século 20, à releitura do gênero conto de fadas tanto na literatura destinada às crianças como no cinema em geral, e no de animação, em particular. Percebemos que o procedimento paródico está presente no processo de releitura, sendo contemplados nesse gesto alguns dos aspectos dos contos de fadas tradicionais, sendo deixados intactos outros elementos. É da indagação sobre como essas narrativas trabalham a releitura dos contos de fadas que partimos para a investigação que motiva este projeto de pesquisa: como a narrativa Shrek!, de William Steig, e sua adaptação para o cinema, pelos estúdios Dreamworks Animation, procedem à releitura do gênero. A pesquisa contemplará, primeiramente, o estudo do gênero conto de fadas, sua estrutura e seus aspectos semânticos, a partir da leitura da narrativa de Steig, para, então, investigar o diálogo textual que esta obra realiza com o gênero de que faz parte. Posteriormente, a narrativa adaptada para o cinema será objeto da investigação para verificarmos como o gênero conto de fadas é relido por esse suporte a partir dos ingredientes fornecidos pela narrativa de Steig. Levaremos em consideração os aspectos estilísticos do discurso, tanto do original em inglês quanto da tradução para o português, por Eduardo Brandão. Com referência à adaptação cinematográfica, procederemos da mesma forma, mas circunscritos nas cenas que focalizaremos como mais importantes para a análise. Partimos do pressuposto de que a versão para o cinema desse conto amplia o procedimento de releitura, estabelecendo um diálogo mais amplo com o próprio gênero. A seguir, focalizaremos a natureza do personagem Shrek, um ogro, para verificar, o processo de grotescalização pelo qual Steig conduz seu texto. Investigaremos como o grotesco contribui para a releitura do gênero tanto na narrativa escrita quanto na sua adaptação para o cinema...
Keywords: Steig, William Shrek! Crítica e interpretação; Literatura infantojuvenil americana - História e crítica; Literatura infantojuvenil americana - Humor, sátiras, etc; Contos de fadas; Parodia; Adaptações para o cinema; Children's literature, American